Functional interventions as augmentation strategies for obsessive-compulsive disorder (OCD): scoping review and expert survey from the international college of obsessive-compulsive spectrum disorders (ICOCS). (1st March 2022) - Varinelli, Alberto; Caricasole, Valentina; Pellegrini, Luca; Hall, Natalie; Garg, Kabir; Mpavaenda, Davis; Dell'Osso, Bernardo; Albert, Umberto; ,; Fineberg, Naomi A.
Abstract: Background: Patients with obsessive-compulsive disorder (OCD) commonly exhibit a range of functional difficulties, presumed linked to neurocognitive changes. Evidence-based first-line treatments have limited effect on improving these cognitive-functional problems. Candidate interventions could be used to augment evidence-based treatments by the multi-professional mental health team. Methods: A scoping review was performed to identify any intervention with at least one peer-reviewed report of clinical improvement in any of the 13 functional domains of the Cognitive Assessment Instrument of Obsessions and Compulsions (CAIOC-13). Next, an online survey of experts of the International College of Obsessive-Compulsive Spectrum Disorders was conducted. Results: Forty-four studies were identified reporting a positive outcome for 27 different kinds of intervention. Twenty-six experts from 12 different countries, including at least one expert from each continent, completed the opinion survey. Five interventions were identified as 'highly promising', none of which was moderated by rater-related factors, suggesting global applicability. Conclusion: Patients with OCD may benefit from a detailed functional assessment, to identify areas of unmet need. A variety of interventions show theoretical promise for treating the complex functional difficulties in OCD as adjuncts to first-line treatments, but the published evidence is weak. Randomised controlled trials are needed to determine the clinical effectiveness of these interventions. Highlights: Functional-cognitive problems are common in patients with OCD. First-line evidence-based treatments have limited effect on these functionalcognitive difficulties. In our scoping review we found 44 studies reporting of improved clinical outcomes in any of the 13 functional domains of the Cognitive Assessment Instrument of Obsessions and Compulsions (CAIOC-13). An online survey of experts of the International College of Obsessive-Compulsive Spectrum Disorders (ICOCS) was conducted and identified five interventions as "highly promising" candidate treatments for functional-cognitive problems in OCD. Randomised controlled trials are needed to determine the clinical effectiveness of these interventions.